2002
DOI: 10.1038/sj.onc.1205273
|View full text |Cite
|
Sign up to set email alerts
|

Alternative transcripts of the candidate tumor suppressor gene, WWOX, are expressed at high levels in human breast tumors

Abstract: The presence of putative tumor-suppressor genes on chromosome 16q23.2-24.1 has been suggested by LOH analysis in several cancer types. This region overlaps with the fragile site FRA16D and the region of homozygous deletions found in several cancer types. The candidate gene WWOX/FOR has been mapped within this region. The mouse homologue of the WWOX protein has been de®ned as an apoptogenic protein and an essential partner of p53 in cell death, supporting WWOX as a tumor suppressor gene candidate. We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
82
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 32 publications
6
82
1
1
Order By: Relevance
“…Carcinoma cell lines and primary tumours exhibit hemizygous or homozygous deletion with end points within fragile regions of the human genome, particularly within the most active common fragile site, FRA3B, encompassed by the FHIT gene . Similarly, for the FHIT gene and the other fragile siterelated genes, deletion at the WWOX (FRA16D) locus and resultant loss of WWOX expression have been shown to promote cell transformation and immortalisation in various human malignancies (Paige et al, 2001;Driouch et al, 2002;Kuroki et al, 2002); however, the incidence of LOH was infrequent in pancreatic carcinoma (Kuroki et al, 2004;Nakayama et al, 2008) and we could not detect LOH in this series of IPMNs (data not shown). Indeed, Fukushige et al (1998) did not detect aberrant copy numbers of DNA sequences on the WWOX locus (16q23.3 -24.1) in pancreatic adenocarcinomas by the comparative genomic hybridisation method.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Carcinoma cell lines and primary tumours exhibit hemizygous or homozygous deletion with end points within fragile regions of the human genome, particularly within the most active common fragile site, FRA3B, encompassed by the FHIT gene . Similarly, for the FHIT gene and the other fragile siterelated genes, deletion at the WWOX (FRA16D) locus and resultant loss of WWOX expression have been shown to promote cell transformation and immortalisation in various human malignancies (Paige et al, 2001;Driouch et al, 2002;Kuroki et al, 2002); however, the incidence of LOH was infrequent in pancreatic carcinoma (Kuroki et al, 2004;Nakayama et al, 2008) and we could not detect LOH in this series of IPMNs (data not shown). Indeed, Fukushige et al (1998) did not detect aberrant copy numbers of DNA sequences on the WWOX locus (16q23.3 -24.1) in pancreatic adenocarcinomas by the comparative genomic hybridisation method.…”
Section: Discussioncontrasting
confidence: 42%
“…Loss of heterozygosity (LOH) at the WWOX locus, hypermethylation of the WWOX regulatory site and resultant reduction of WWOX expression have been reported in various human malignancies (Paige et al, 2001;Driouch et al, 2002;Kuroki et al, 2002;Iliopoulos et al, 2005). Indeed, restoration of the WWOX gene suppresses cell proliferation and induces apoptosis in various human malignancies, including in cells derived from lung cancer (Fabbri et al, 2005), prostate cancer (Qin et al, 2006) and breast cancer (Aqeilan et al, 2007).…”
mentioning
confidence: 99%
“…However, the lack of mutations in the second allele in cancer cells and the sometimes elevated rather than diminished level of expression of the gene in cancer cells have led some to conclude that the WWOX gene does not encode a 'classical' tumour suppressor (Watanabe et al, 2003). While the normal function of WWOX is currently unknown, its aberrant expression in a variety of cancer cell types has been extensively reported, also suggesting a likely association with cancer cell biology Paige et al, 2001;Yakicier et al, 2001;Driouch et al, 2002;Kuroki et al, 2002;Ishii et al, 2003;Yendamuri et al, 2003;Aqeilan et al, 2004a;Guler et al, 2004;Kuroki et al, 2004).…”
mentioning
confidence: 99%
“…The genetic events leading to high b-catenin activity in breast cancer have not yet been elucidated. We hypothesized that the lack of WWOX expression, which is frequent in breast cancer tissues (Driouch et al, 2002;Guler et al, 2004Guler et al, , 2005Chang et al, 2005), might constitutively stimulate the Wnt/b-catenin pathway and thereby contribute to enhancing tumor growth. Our observation that knockdown of WWOX enhances Wnt-3a transcriptional activity, as well as that WWOX overexpression inhibits Dvl-1 transcriptional activity in MCF-7 and BT474 cells, supports this hypothesis.…”
Section: Functional Interaction Between Wwox and Wnt Pathway N Bouteimentioning
confidence: 99%
“…The decrease of WWOX expression is frequently associated with a worse clinical outcome for patients (Pluciennik et al, 2006;Hezova and Ehrmann JKolar 2007;Aqeilan et al, 2007a). Several tumor types, such as human breast tumors, overexpress aberrant transcripts (Driouch et al, 2002;Ludes-Meyers et al, 2003). Moreover, WWOX has the capacity to function as a tumor suppressor gene both in vitro and in vivo (Bednarek et al, 2001;Kuroki et al, 2004;Fabbri et al, 2005;Iliopoulos et al, 2007;LudesMeyers et al, 2007;Qin et al, 2007;Aqeilan et al, 2007bAqeilan et al, , 2007c.…”
Section: Introductionmentioning
confidence: 99%